Kecanduan Game Online sebagai Ancaman Keharmonisan Rumah Tangga - Henky Ade Irawan; Khoirul Ahsan (Cakrawala: Journal of Religious Studies and Global Society, 2025)
This study aims to determine the impact of online gaming addiction on emotional relationships within household harmony in Sukamakmur Village. The approach used is qualitative, employing in-depth interviews with five informants consisting of four wives and one husband. The findings reveal that online gaming addiction negatively affects spousal communication, emotional engagement, and the fulfillment of family roles. The addiction is characterized by excessive gaming duration, neglect of family responsibilities, and heightened emotional conflict. These conditions result in decreased household harmony, including reduced family time and increased arguments. Efforts made by couples to address this issue include open communication, setting gaming time limits, and seeking family counseling. This study emphasizes the importance of digital awareness and the active role of partners in maintaining emotional balance within families in the digital age.